1993
DOI: 10.1111/j.1600-0897.1993.tb00620.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Fetal Trisomies 21 and 18 From Maternal Blood Using Triple Gradient and Magnetic Cell Sorting

Abstract: Our new approach for noninvasive prenatal diagnosis has proven to be reliable in this first series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
140
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(146 citation statements)
references
References 12 publications
4
140
2
Order By: Relevance
“…Our findings are at variance to those of Gänshirt-Ahlert et al 12,13 , who also used triple density gradient centrifugation and anti-CD71 magnetic cell sorting to enrich fetal cells in maternal blood and reported no significant difference in the number of erythroblasts between pre-CVS and post-CVS samples. In contrast, Jansen et al 14 , who isolated fetal cells by Ficoll single density centrifugation and maternal depletion with CD45 and CD14 and CD71 magnetic cell sorting enrichment and then applied FISH for the Y-chromosome, from blood samples obtained immediately before and 5 -20 minutes after CVS, found an increase in the number of fetal cells in 10 out of 19 male pregnancies examined.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Our findings are at variance to those of Gänshirt-Ahlert et al 12,13 , who also used triple density gradient centrifugation and anti-CD71 magnetic cell sorting to enrich fetal cells in maternal blood and reported no significant difference in the number of erythroblasts between pre-CVS and post-CVS samples. In contrast, Jansen et al 14 , who isolated fetal cells by Ficoll single density centrifugation and maternal depletion with CD45 and CD14 and CD71 magnetic cell sorting enrichment and then applied FISH for the Y-chromosome, from blood samples obtained immediately before and 5 -20 minutes after CVS, found an increase in the number of fetal cells in 10 out of 19 male pregnancies examined.…”
Section: Discussioncontrasting
confidence: 56%
“…In contrast, Jansen et al 14 , who isolated fetal cells by Ficoll single density centrifugation and maternal depletion with CD45 and CD14 and CD71 magnetic cell sorting enrichment and then applied FISH for the Y-chromosome, from blood samples obtained immediately before and 5 -20 minutes after CVS, found an increase in the number of fetal cells in 10 out of 19 male pregnancies examined. Possible reasons for the difference in findings in the studies of Gänshirt-Ahlert et al 12,13 are that firstly, the pre-CVS and post-CVS blood samples were obtained from two different groups of women; secondly, the range of gestational age of the pregnancies examined was not indicated, particularly in relation to the similarity of gestation of the two groups, and previous studies have shown a biological variation in the number of fetal cells present in maternal blood at different gestations 17 -19 ; and thirdly, the distribution of normal and abnormal karyotype in the pregnancies examined before and after CVS is not given and it is known that in trisomic pregnancies the number of fetal cells in maternal blood is increased 6,7 .…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Many methods like Fluorescence Activated Cell Sorting (FACS), Magnetic Activated Cell Sorting (MACS), charge flow separation, immunofluorescent beads, lectins, etc. have been exploited for the isolation of fetal nucleated red blood cells (NRBCs) from maternal peripheral blood (1)(2)(3)(4)(5). Of these, FACS has been the most widely used technique.…”
mentioning
confidence: 99%